A high propensity for excessive daytime sleepiness independent of lifestyle is associated with cognitive performance in community-dwelling older adults - Wu, Junxin; Wu, Zijing; Xie, Caixia; Lin, Yongsheng; Fu, Zhiqiang; Zhu, Limao; Qi, Wei; Wang, Huali (Frontiers in Psychiatry, 2023)
Objective The relationship between excessive daytime sleepiness (EDS) and cognitive performance of older adults remains unclear, especially when a healthy lifestyle is considered. The study aimed to explore the association between EDS in passive and active situations and general cognitive function among community-dwelling older adults. Methods Two hundred and seventy-one older adults aged 60 and above were recruited from the community cohort in Shangrao. All study participants were free of depression and dementia. The Chinese version of the Epworth Sleepiness Scale (CESS) was used to evaluate EDS. Using the item scores of CESS, the presence of EDS among all study participants were grouped as non-EDS, passive situation-related EDS (PSR-EDS), active situation-related EDS (ASR-EDS), and high sleep propensity (HSP). The Hong Kong Brief Cognitive Test (HKBC) was used to assess cognitive function. Chinese healthy lifestyle metrics were scored based on AHA Life Simple-7. The multivariate logistic regression model was used to estimate the association between the presence of EDS and cognitive function. Results The PSR-EDS (n = 29, 20.8 ± 5.3) and the HSP groups (n = 21, 19.8 ± 4.8) scored lower with HKBC than in the non-EDS group (n = 213, 23.2 ± 4.9). The subdomain performance of language in the HSP group was poorer than in the non-EDS group (ps < 0.05). Relative to non-EDS, HSP (OR = 3.848, 95% CI = 1.398-10.591) was associated with an increased risk of poor cognitive performance after adjusting age, sex, education, and healthy lifestyle metrics. Conclusion High propensity for excessive daytime sleepiness, irrespective of lifestyle, is associated with poorer cognitive performance among community-dwelling older adults. The findings may provide empirical evidence to support sleepiness intervention for reducing the risk of cognitive decline.